A BRIEF MENTION OF BHOOT VIDYA (PSYCHOTHERAPY) IN SUSRUTA SAMHITA BY ACHARYA SUSRUTA - Basumatary, *Khagen; Lairikyengbam, Sujalata devi; Bhatta, Chumi; Loukrakpam, Victoria Devi (International Journal of Ayurveda and Pharma Research, 2018)
Ayurveda is a system of medicine with historical roots in the Indian sub continent. It gets originated from Atharvaveda which get ramified into Astanga Ayurveda (8 branches of Ayurveda). They are Shalya, Shalakya, Kayachikitsa, Bhootavidya, Koumarbhritya, Agadatantra, Rasayan tantra, Bajikarantantra. According to Susruta, Bhoota Bidya means the branch of Ayurveda which deals with the diseases caused by Deva, Daitya, Gandharva, Yaksha, Rakshas, Pitar, Pisash, Naag etc and their treatment by Santipath, Balipradan, Havan etc is defined as Bhutavidya. Susruta Samhita though deals or covers all the 8 branches of Astanga Ayurveda but it emphasis more on Shalya Chikitsa. The Bhoota Vidya related topics are all scattered in Susruta Samhita and make it hard for the readers to find out their topics. So, for the convenience of the reader and to make it updated with the changing present era and easily accessible, the present work has been carried out. In 27 chapters of Susruta Samhita has Bhoot Bidya related topics. Sutrasthan contain 9 chapters, Sharir Sthan contains 1 chapter, Chikitsa Sthan contains 2 chapters and Uttar Tantra contains 15 chapters. Compiling the scattered topics of Bhuta Bidya available in Susruta Samhita will make the reader easy to choose its topic of interest in Susruta Samhita regarding the Bhuta Bidya related topics and it also helps further in research works.